2023
DOI: 10.14379/iodp.proc.396.103.2023
|View full text |Cite
|
Sign up to set email alerts
|

Site U1565

Abstract: Contents 1 Background and objectives 3 Operations 5 Lithostratigraphy 9 Biostratigraphy 12 Paleomagnetism 17 Geochemistry 21 Physical properties 24 References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The liner correction of 66/58 = 1.138 should be applied to the WRMSL GRA bulk densities (see Physical properties in the Expedition 396 methods chapter [Planke et al, 2023a]). The value of the liner correction was confirmed for the granitic cores recovered at Site U1565 (see Physical properties in the Site U1565 chapter [Planke et al, 2023b]).…”
Section: Unit Iii: Basementmentioning
confidence: 67%
See 3 more Smart Citations
“…The liner correction of 66/58 = 1.138 should be applied to the WRMSL GRA bulk densities (see Physical properties in the Expedition 396 methods chapter [Planke et al, 2023a]). The value of the liner correction was confirmed for the granitic cores recovered at Site U1565 (see Physical properties in the Site U1565 chapter [Planke et al, 2023b]).…”
Section: Unit Iii: Basementmentioning
confidence: 67%
“…Site U1566 is a companion site to Site U1565. Both sites are located on the western flank of the Kolga High (see Figure F1 in the Site U1565 chapter [Planke et al, 2023b]) about 1 km apart at a water depth just above 2000 m. The Kolga High is one of several areas along the rifted margin characterized by a thin sediment cover above the top basalt surface and a rapidly westward shoaling of the Base Cretaceous Unconformity (BCU) (Zastrozhnov et al, 2020) (for a summary, see Background and objectives in the Site U1565 chapter [Planke et al, 2023b]).…”
Section: Background and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre‐drilling seismic interpretation suggested that the volcanic rocks might be retained on top of thick Cretaceous‐Palaeocene sedimentary layers (Gernigon et al., 2021; Manton et al., 2018; Millett et al., 2022; Zastrozhnov et al., 2020). The IODP Expedition 396 revealed, however, the unexpected presence of altered granitic ‘basement rocks’ beneath Quaternary sediments in Holes U1565A/B and beneath older basaltic cover in Hole U1566A (Figure 1) (Planke et al., 2023a, 2023b).…”
Section: Introductionmentioning
confidence: 99%